RELATIONSHIP BETWEEN CLASSROOM RULES AND DISCIPLINE OF STUDENTS IN SELECTED SECONDARY SCHOOLS IN KALIRO DISTRICT; A DESCRIPTIVE CORRELATIONAL AND CROSS-SECTIONAL STUDY. - Nakiranda , Shamimu; Bakashaba, Edmand; Ssendagi, Muhammad (Student’s Journal of Health Research Africa, 2023)
Background: This study aims to explore the relationship between classroom rules and the discipline of students in selected secondary schools in the Kaliro district. Methodology: A descriptive correlational and cross-sectional survey design was used. The study used a mixed research approach where both quantitative and qualitative data were collected and analyzed. The target population comprised five secondary schools in Kaliro District. The study used the Board of Governors members, head teachers, students, and teachers of the selected secondary schools as participants for the study. A target of 411 participants was used. The researcher adopted a table of determining sample size and 198 respondents were selected as respondents of the study. Results: Based on findings classroom rules are less implemented in selected schools as absent students, vulgar, vandalism, and noise-making go unpunished by the school management. This further confirms that classroom rules have a relationship with the discipline of students as most school rules are silent and indiscipline high in selected secondary schools in Kaliro District. There is a significant relationship between classroom rules and the discipline of students in selected secondary schools in Kaliro District. The correlation between classroom rules and discipline of students in selected secondary schools in Kaliro District was 0.728 with a sig value of 0.001. This indicates a positive significant relationship between classroom rules and the discipline of students. Therefore, implementation of school rules discourages students from being indisciplined. Conclusion: There is a significant relationship between classroom rules and the discipline of students and thus classroom rules influence how students behave at school in Kaliro District. Recommendation: The school board of governors should also come up with policies for rewarding well-disciplined students to encourage others to improve their behaviors in the school.